Islam and Music: Special Reference to the Concept of Moderation and the Enjoyment Music - Awang, Idris bin; Hj. Ab. Majid, Mohammad Kamil bin; Yusof, Muhammed bin (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The art of music is not alien to Islam. Many Muslim scholars have written about it and some were even musicians. There are many views among both Muslims and non-Muslims concerning the status of music in Islam. Some affirm Islam’s approval of music, while other many see Islam’s negation of it. This interest is due to the emergence of various genre of music in the cultures and societies of the modern world today. The discussion in this paper is an attempt to explain the current situation of this polemic. As we see it, Islam views the art of music as universal and not exclusive to any particular race, culture or nation. To say that a particular genre of music in Islamic or otherwise would depend upon the criteria as expounded by Muslim scholars. This means that anyone can be seriously involved in music so long as it does not contravene the teachings of Islam. This paper will also attempt to explain the place of moderation in the enjoyment of music within the parameters set by Islam with the view of fulfilling human aesthetic needs.